2020
DOI: 10.9734/arjass/2020/v10i430154
|View full text |Cite
|
Sign up to set email alerts
|

Marital Distress among Police Personnel in Awka Metropolis: The Influence of Argument and Self-efficacy

Abstract: The study investigated whether argument and self-efficacy would have an influence on marital distress among police personnel. A total number of one hundred and ninety-seven (197), Nigeria police force (NPF) personnel working in Police headquarters; served as participants for the study. They were selected using non-probability sampling (convenient sampling techniques). They consist of 87(44.2%) females and 110 (58.5%) males; their age ranged from 22-51 years and their mean age was 34.94 with standard deviation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Self-e cacy refers to an individual's level of con dence in his or her ability to perform a given task through his or her own abilities [11], and if an individual's level of con dence is higher, the higher his or her self-e cacy will be. Research has shown that physical activity can increase an individual's selfe cacy [12], and that individuals' participation in physical activity can improve their self-con dence and willpower, which in turn improves their health [13]. Self-e cacy is also an important in uence on an individual's physical health.…”
Section: Introductionmentioning
confidence: 99%
“…Self-e cacy refers to an individual's level of con dence in his or her ability to perform a given task through his or her own abilities [11], and if an individual's level of con dence is higher, the higher his or her self-e cacy will be. Research has shown that physical activity can increase an individual's selfe cacy [12], and that individuals' participation in physical activity can improve their self-con dence and willpower, which in turn improves their health [13]. Self-e cacy is also an important in uence on an individual's physical health.…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy refers to an individual's level of confidence in his or her ability to perform a given task through his or her own abilities [17], and if an individual's level of confidence is higher, the higher his or her self-efficacy will be. Research has shown that physical activity can increase an individual's self-efficacy [18], and that individuals' participation in physical activity can improve their selfconfidence and willpower, which in turn improves their health [19]. Self-efficacy is also an important influence on an individual's physical health.…”
mentioning
confidence: 99%